Efficacy and safety of combined ethinyl estradiol/drospirenone oral contraceptives in the treatment of acne - Jerry KL Tan; Chemanthi Ediriweera (Dove Medical Press, 2009)
Jerry KL Tan1, Chemanthi Ediriweera21University of Western Ontario and Windsor Clinical Research Inc., Windsor, Ontario, Canada; 2University of Western Ontario, Southwest Ontario Medical Education Network, Windsor, Ontario, CanadaAbstract: Acne is a common disorder affecting the majority of adolescents and often extends into adulthood. The central pathophysiological feature of acne is increased androgenic stimulation and/or end-organ sensitivity of pilosebaceous units leading to sebum hypersecretion and infundibular hyperkeratinization. These events lead to Propionibacterium acnes proliferation and subsequent inflammation. Hormonal therapy, including combined oral contraceptives (OCs), can attenuate the proximate androgenic trigger of this sequence. For many women, hormonal therapy is a rational option for acne treatment as it may be useful across the spectrum of severity. Drospirenone (DRSP) is a unique progestin structurally related to spironolactone with progestogenic, antimineralocorticoid, and antiandrogenic properties. It is available in 2 combined OC preparations (30 µg EE/3 mg DRSP; Yasmin® in a 21/7 regimen; and 20 µg EE/3 mg DRSP; Yaz® in a 24/4 regimen). These preparations are bereft of the fluid retentional side effects typical of other progestins and their safety has been demonstrated in large epidemiological studies in which no increased risk of vascular thromboembolic disease or arrhythmias was observed. In acne, the efficacy of DRSP-containing OCs has been shown in placebo-controlled superiority trials and in active-comparator non-inferiority trials.Keywords: acne vulgaris, combined oral contraceptives, drosperinone, ethinyl estradiol, efficacy, safety, treatment